A 52-year-old man with abdominal pain and distension - Rahiminejad, Mohammad Ehsan; Moaddab, Amirhossein (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Rahiminejad ME, Moaddab A. A 52-year-old man with abdominal pain and distension. Turk J Gastroenterol 2017; 28: 314-5.